PERLINDUNGAN HUKUM TERHADAP PELAKU USAHA PEDAGANG KAKI LIMA DALAM MENJALANKAN USAHANYA DI KOTA MATARAM - Baehaki Syakbani (Sekolah Tinggi Ilmu Ekonomi AMM, 2018)
Street Traders (PKL) is a people's economic activity, which is used to refer to a person (trader) who sells goods or food in the empire shops, sidewalks by using stalls or wheelbarrows. The problems raised in this research can be formulated as follows: What are the constraints of Business Traders of Street Traders in running their business in Mataram City? And How to Form Legal Protection of Business Traders of Street Vendors in Running Their Business in Mataram City? The research used in the research is normative-empirical law research, research conducted by reviewing the provisions of legislation (inabstracto) and see the legal facts that occur in the field (inconcreto). From the results of the research found the discussion in the problems studied include: Constraints of Business Actor Street Traders in running their business in the city of Mataram, namely: a. Low awareness of street vendors law, b. Weak Supervision by Enforcement Officials, c. Relocation of street vendors that are not strategic and adequate, d. Economic Factors of street vendors, and the form of legal protection against business players of street vendors in carrying out their business in Mataram city that has been regulated in the Regional Regulation of Mataram No10 Year 2015 on Street Traders. And suggestions For the Government, to be more active in providing protection for street vendors who run their business in the city of Mataram, and the government is more set against the shops in the city of Mataram for street vendors no less compete with them